Legitimate differences : interpretation in the abortion controversy and other public debates - Warnke, Georgia (Berkeley, Calif. : University of California Press, 1999)
Legitimate Differences challenges the usual portrayal of current debates over thorny social issues including abortion, pornography, affirmative action, and surrogate mothering as moral debates. How can it be said that our debates oppose principles of life to those of liberty, principles of liberty to those of equality, principles of equality to those of fairness, and principles of fairness to those of integrity, when we as Americans share all the.
Interpretation and social issues -- Surrogate mothering and the meaning of family -- Affirmative action, neutrality, and integration -- Interpretive differences and the abortion debate -- Pornography, ideology, and silence -- Hermeneutic debate and deliberative democracy -- Tradition and ethical knowledge -- Conclusion.
Includes bibliographical references (pages 195-210) and index.
Print version record.
English.
JSTOR
Keywords: Social ethics -- United States; Social values -- United States; United States -- Social policy -- Moral and ethical aspects; Hermeneutics; Social psychology; Parents; Culture; Humanities; Families; Nuclear families; Ethnic groups; Human rights; Sociology; Comparative government; Mass media; Obstetrics -- Surgery; Social control; Social sciences; Surgery, Operative; Race; Ethnology; Anthropology; Medical care; Civil rights; Surrogate mothers; Surrogate motherhood; Bioethics; Liberty; Abortion; Democracy; Prejudices; Social justice; Philosophy; Cultural pluralism; Social problems; Literature; Literature, Modern; Social values; Black People; Psychology, Social; Social Control Policies; Parents; Culture; Humanities; Family; Ethnicity; Human Rights; Sociology; Ethics; Principle-Based Ethics; Political Systems; Communications Media; Obstetric Surgical Procedures; Social Control, Formal; Social Sciences; Behavior and Behavior Mechanisms; Information Science; Public Policy; Population Groups; Persons